THE EFFECT OF THE SERVQUAL DIMENSION ON CUSTOMER SATISFACTION OF PT PLN (PERSERO) UID SULUTTENGGO, ULP SOUTH MANADO - Musak, Priscilla; Willem J. F. A. Tumbuan; Djurwati Soepeno (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Marketing in the Development of New and Renewable Energy (NRE) is currently focused on enhancing public understanding, acceptance, and utilization of clean energy sources. In line with this, the present study aims to analyze the influence of the SERVQUAL dimensions on customer satisfaction at PT PLN (Persero) UID Suluttenggo, specifically at the South Manado Customer Service Unit (ULP Manado Selatan). The sample for this study was determined using purposive sampling, drawn from a population of 103,093 customers. The sample size was calculated using Slovin’s formula, resulting in 100 respondents. A quantitative research method was employed, with data analysis techniques including validity and reliability tests, classical assumption tests, hypothesis testing, and multiple linear regression analysis. The results of the study indicate that all five SERVQUAL dimensions-Tangibles, Reliability, Responsiveness, Assurance, and Empathy-simultaneously have a positive and significant effect on customer satisfaction at PT PLN (Persero) UID Suluttenggo, ULP Manado Selatan. Individually, each dimension also shows a positive and significant impact on customer satisfaction. These findings imply that improving service quality across each SERVQUAL dimension directly contributes to increased customer satisfaction. Therefore, the company must provide balanced attention to all dimensions—not only focusing on physical aspects and service facilities (Tangibles) but also addressing non-technical aspects such as service reliability (Reliability), responsiveness to customer needs (Responsiveness), assurance and sense of security (Assurance), and an empathetic attitude in service delivery (Empathy). Continuous improvement in all five dimensions is believed to strengthen the company’s relationship with its customers, enhance customer loyalty, and build a positive image of PT PLN (Persero) in the public eye. Keywords: Tangibles, Reliability, Responsiveness, Assurance, Empathy, Customer Satisfaction